1998
DOI: 10.1080/07315724.1998.10718779
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Smoking on Vitamin C Status During the Third Trimester of Pregnancy and on Vitamin C Levels in Maternal Milk

Abstract: If the concentration of antioxidants (vitamin C) in smokers' breast milk is also lower, this might aggravate the peroxidation problems of their newborn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
1
3

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 18 publications
1
24
1
3
Order By: Relevance
“…Nutrient intake is decreased in pregnant women as compared to non pregnant women [38] . It is possible that dietary vitamin C intake may have been lower in our studied population than in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Nutrient intake is decreased in pregnant women as compared to non pregnant women [38] . It is possible that dietary vitamin C intake may have been lower in our studied population than in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20] Importantly, this study revealed inferior antioxidant properties of breast milk from smoking mothers. This finding substantiates further research on the effects of inferior antioxidant properties of breast milk on the health status of infants born to smoking mothers.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin C deficiency could lead to inadequate antioxidant defence. Moreover, the lower vitamin C 18 and E 16 concentrations in the milk of smoking mothers could mean their children face an even greater challenge.…”
mentioning
confidence: 99%